2004
DOI: 10.1002/dmrr.428
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of the β‐cell dysfunction in diabetic APA hamsters by antioxidants and AGE inhibitor treatments

Abstract: These data suggest that NAC and PM treatment of SZ-injected diabetic hamsters reduces oxidative stress and restores beta-cell function, but that AG treatment has little beneficial effect on the diabetic conditions of SZ-injected hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…52 In both of these studies, high levels of AGEs were shown to result in hyperglycemia. Given that prooxidants such as AGEs are toxic to pancreatic islets [53][54][55] and that anti-AGE agents and diets protect against islet and ␤-cell injury and dysfunction, 30,53 it is possible that AGER1 overexpression could protect against ␤-cell injury as a matter of course. Further studies are required to elucidate the mechanisms involved in these effects.…”
Section: Discussionmentioning
confidence: 99%
“…52 In both of these studies, high levels of AGEs were shown to result in hyperglycemia. Given that prooxidants such as AGEs are toxic to pancreatic islets [53][54][55] and that anti-AGE agents and diets protect against islet and ␤-cell injury and dysfunction, 30,53 it is possible that AGER1 overexpression could protect against ␤-cell injury as a matter of course. Further studies are required to elucidate the mechanisms involved in these effects.…”
Section: Discussionmentioning
confidence: 99%
“…A vitamin B-6-deficient diet increases plasma lipid peroxidation and decreases plasma vitamins E and C concentrations in rats (45). Experimental models have further shown that supplementation with vitamin B-6 suppresses the colonic concentrations of 8-OHdG induced by colonic carcinogen (46) and decreases plasma 8-OHdG and malonaldehyde in hyperglycemia-induced oxidative stress (37). Vitamin B-6 compounds can prevent the oxygen radical generation and lipid peroxidation caused by hydrogen peroxide in U937 monocytes as well (47).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B-6 deficiency has been shown to cause degenerative changes in b cells in the islets of Langerhans and to decrease both pancreatic and circulating insulin (35,36). Likewise, pyridoxamine treatment of streptozotocin-induced diabetic hamsters improves glucose tolerance and restores b cell function (37). Moreover, supplementation with pyridoxine lowers blood glucose and decreases Hb A lc in diabetic patients (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mitochondrial dysfunction may contribute to the development of type 2 diabetes (4). Furthermore, diabetic hamsters treated with inhibitors of advanced glycation end products (AGEs) showed reduced oxidative stress and restored pancreatic ␤-cell function (7). However, the mechanism underlying the development of type 2 diabetes, how that mechanism relates to DNA damage, and how type 2 diabetes increases the risk of CVD are not well understood.…”
mentioning
confidence: 99%